Driving small-scale fisheries in developing countries - Purcell, Steven W.; Pomeroy, Robert S. (Frontiers in Marine Science, 2015)
Small-scale fisheries (SSFs) engage the vast majority of the world’s fishers but are struggling to keep pace with coastal populations, and stocks are declining to levels that threaten reproductive capacity. The provision of food and livelihoods to low-income fishers into the future will be unlikely without radical changes to fisheries policy. We draw on repeating analogies of driving a car to illustrate fundamental reforms needed for driving (managing) small-scale fisheries. SSFs will continue to be unsustainable by relying too heavily on output controls (the ‘brake’). Managers need to move away from routinely using moratoria (i.e. the ‘handbrake’) as a management measure, although these measures may be needed as a last resort. Scientists (‘backseat drivers’) must engage more directly with fishery management agencies to understand their constraints and needs. Resource managers must come to terms with regulating fishing inputs (the ‘accelerator’) by imposing limited-entry rules, vessel limitations or short fishing seasons in addition to sensible output controls. Reforms to resource management will need to entail unpopular measures if small-scale fisheries are to deliver sustained benefits to fishing communities into the future.